Bir Çocuk Hastada Foley Sonda ile Özofagustan Yabancı Cisim Çıkarılmasının Nadir bir Komplikasyonu: Özofagus Rüptürü - Tartar, Tugay; Bakal, Ünal; Saraç, Mehmet; Eroğlu, Yeşim; Kazez, Ahmet (Kahramanmaras Sutcu Imam University, 2021)
Özofagus yabancı cisimlerinde (YC) tanı ve tedavinin gecikmesi morbidite ve mortaliteyi artırır. Tanıda anamnez, radyolojik görüntüleme ve endoskopi önemlidir. Dokuz aylık erkek hasta bir saat önce madeni para yutma şikayetiyle hastaneye başvurmuş. Akciğer grafisinde özofagus 2. darlıkta görülen YC foley sonda ile çıkarılmış. YC’nin çıkarılmasından 6 saat sonra boyun ve göğüs kısmında şişlik gelişmesi üzerine acil servise başvurdu. Fizik muayenede toraks ön duvarında cilt altı krepitasyon mevcuttu. Özofagografide kontrast maddenin özofagus sağ lateralden göğüs boşluğuna kaçtığı görüldü. Skopi eşliğinde nazogastrik sonda takıldı, orali kapatıldı ve antibiyoterapi başlandı. Konservatif takibin 7. gününde genel durumunun bozulması ve floroskopide kontrast madde kaçağının devam etmesi üzerine torakotomi ile özefagus primer onarımı yapıldı. Sonuç olarak, Özofagus YC’lerinin çıkarılmasında foley sonda kullanımı ciddi komplikasyona yol açabilir.

Delay in diagnosis and treatment of esophageal foreign bodies (FBs) increases morbidity and mortality. Anamnesis, radiological imaging and endoscopy are important in this diagnosis. A nine-month-old male patient was admitted to the hospital an hour after swallowing a coin. Pulmonary radiographic images detected the FB in the 2nd narrowing of the oesophagus and the FB was removed using a foley catheter. Six hours after removal of the FB, the patient was re-admitted by the emergency service upon development of puffiness in the neck and chest area. Physical examination revealed subcutaneous crepitation on the anterior wall of the thorax. Esophagography revealed that the contrast agent leaked from the right lateral of the oesophagus into the chest cavity. The nasogastric tube was inserted, the oral nutrition was stopped and antibiotherapy was started. Primary oesophagus repair was performed via thoracotomy on the 7th day of conservative follow-up upon the deterioration of the general condition and continuing leakage of contrast agent as observed in the fluoroscopy. In conclusion, The use of foley catheter in the removal of esophageal FBs can lead to serious complications.
A Rare Complication of Foreign Body Removal from the Oesophagus Using Foley Catheter: Esophageal Rupture
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi